Metabolizable energy levels for semi-heavy laying hens at the second production cycle Níveis de energia metabolizável para poedeiras semipesadas no segundo ciclo de produção - Fernando Guilherme Perazzo Costa; Janaine Sena da Costa; Cláudia de Castro Goulart; Denise Fontana Figueiredo-Lima; Raul da Cunha Lima Neto; Bárbara Josefina de Sousa Quirino (Revista Brasileira de Zootecnia, 2009)
This study was carried out to evaluate the energy levels in the diet to obtain better performance rates and quality of eggs from laying hens in the second production cycle. One hundred and eighty Bovans Goldline laying hens with 62 weeks of age were used during four 28-day periods. A completely randomized experimental design was used with four metabolizable energy levels (2,650, 2,725, 2,800, 2,875 and 2,950 kcal/kg), each with six replicates of six birds. The energy level of diet did not affect the weight of the egg, yolk, albumen and eggshell, the percentages of yolk, albumen and eggshell, yolk color and egg specific gravity. Feed intake, egg production, egg mass and feed conversion per egg mass and per dozen eggs increased significantly with increasing levels of metabolizable energy. Feed intake decreased linearly as the energy level in the diet increased. The metabolizable energy levels showed a quadratic effect on egg production, egg mass and feed conversion per egg mass and per dozen eggs. The metabolizable energy level of 2,830 kcal/kg was the most appropriate to promote better performance and quality of eggs from laying hens in the second production cycle. Este estudo foi realizado com o objetivo de avaliar níveis energéticos na dieta para obtenção de melhores índices de desempenho e qualidade de ovos de poedeiras de segundo ciclo de produção. Utilizaram-se 180 poedeiras com 62 semanas de idade, da linhagem Bovans Goldline, durante quatro períodos de 28 dias. O delineamento utilizado foi o inteiramente casualizado, com quatro níveis de energia metabolizável (2.650, 2.725, 2.800, 2.875 e 2.950 kcal/kg de ração), cada um com seis repetições de seis aves. O nível energético da dieta não influenciou os pesos do ovo, da gema, do albúmen e da casca, as porcentagens de gema, albúmen e casca, a coloração da gema e a gravidade específica do ovo. O consumo de ração, a produção de ovos, a massa do ovo e a conversão por massa de ovo e por dúzia de ovo aumentaram significativamente com o aumento dos níveis de energia metabolizável. O consumo de ração reduziu de forma linear conforme aumentou o nível de energia na ração. Os níveis de energia metabolizável tiveram efeito quadrático sobre a produção, a massa do ovo e a conversão por massa e por dúzia de ovo. O nível de energia metabolizável de 2.830 kcal/kg foi o que promoveu melhor desempenho e qualidade do ovo de poedeiras no segundo ciclo de postura.